If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23y + -500 = 73y + -100 Reorder the terms: -500 + 23y = 73y + -100 Reorder the terms: -500 + 23y = -100 + 73y Solving -500 + 23y = -100 + 73y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-73y' to each side of the equation. -500 + 23y + -73y = -100 + 73y + -73y Combine like terms: 23y + -73y = -50y -500 + -50y = -100 + 73y + -73y Combine like terms: 73y + -73y = 0 -500 + -50y = -100 + 0 -500 + -50y = -100 Add '500' to each side of the equation. -500 + 500 + -50y = -100 + 500 Combine like terms: -500 + 500 = 0 0 + -50y = -100 + 500 -50y = -100 + 500 Combine like terms: -100 + 500 = 400 -50y = 400 Divide each side by '-50'. y = -8 Simplifying y = -8
| 3k-17=4 | | 15ab-32ab^2= | | -6p+11=2p-13 | | 2(2f+4)=4(f+2) | | 1-2(3a-5)=3(-2a+1)+8 | | 16t^2-484=0 | | 12x+8=7x+2 | | x+6=6x-66 | | 16y+2x=18 | | -7(-3x-6)=84 | | 16x+2y=18 | | 4x-5-2x= | | .5(y+6)-3=8 | | 0.3-15=0.2x-5 | | -4m+5=-2m-15 | | 2x+7=39-6x | | (4-1)m-m=(m-1)8*4 | | s=15p | | 2x+5=41-x | | 3(6x-1)-2(x+3)=8(x+1) | | 2x+8y-26=0 | | 3(x^2-x)=3x^2+5x-11 | | (8x-10)+(6X)+(10x+10)= | | 7(u+2)=4u+35 | | 4x+2=7x-9 | | r+7=20 | | 6x+5=-115-4x | | -32=4(9x-3) | | 63x^3-7x=0 | | -7w+5(w+3)=21 | | 12x-17=28 | | -11.7x=105.3 |